2009
DOI: 10.3390/s90907266
|View full text |Cite
|
Sign up to set email alerts
|

Semiconductor Quantum Dots in Chemical Sensors and Biosensors

Abstract: Quantum dots are nanometre-scale semiconductor crystals with unique optical properties that are advantageous for the development of novel chemical sensors and biosensors. The surface chemistry of luminescent quantum dots has encouraged the development of multiple probes based on linked recognition molecules such as peptides, nucleic acids or small-molecule ligands. This review overviews the design of sensitive and selective nanoprobes, ranging from the type of target molecules to the optical transduction schem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
229
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 428 publications
(231 citation statements)
references
References 94 publications
(102 reference statements)
1
229
0
1
Order By: Relevance
“…Since the fast flow speed of the CdSe/ZnS QDs is faster than that of the dye in the NAP-5 column, this result indicates that the unreacted CdSe/ZnS QDs were removed after the separation method using the NAP-5 column. Many previous papers demonstrated similar types of pH sensors; 34,35 however, this result indicates that this separation process is an important process to achieve the correct fluorescence spectrum of the reacted CdSe/ZnS QDs-dye.…”
Section: Resultsmentioning
confidence: 87%
“…Since the fast flow speed of the CdSe/ZnS QDs is faster than that of the dye in the NAP-5 column, this result indicates that the unreacted CdSe/ZnS QDs were removed after the separation method using the NAP-5 column. Many previous papers demonstrated similar types of pH sensors; 34,35 however, this result indicates that this separation process is an important process to achieve the correct fluorescence spectrum of the reacted CdSe/ZnS QDs-dye.…”
Section: Resultsmentioning
confidence: 87%
“…182,183 QD-based microfluidic protein chip detection and optically addressed fluorescence resonance energy transfer (FRET) probes are being used in signal transduction to design the detection systems for nucleic acids, proteins, peptides, and small molecules. 184,185 The increased number of acceptors linked to QDs can significantly amplify the signal of the target through enhanced energy-transfer efficiency. This ultrasensitive nanoprobe based on the FRET system had the capability to detect low concentrations of DNA, which have great potential to diagnose DNA mutations of tumor cells in clinical samples.…”
Section: Nanotech In Anticancer Researchmentioning
confidence: 99%
“…[27][28][29][30] Correspondingly, based on ideas of the self-assembly discussed above, the combination of the two directions, that is the anchoring of functional organic molecules (including tetrapyrrolic compounds and other heteromacrocycles) or molecular complexes or even proteins to QDs, is of considerable scientific and a wide practical interest including material science and biomedical applications. [31][32][33][34][35][36][37][38] Inspired by our earlier work on self-assembled multiporphyrin arrays [39][40][41][42][43][44][45] we have elaborated the experimental approach in the direct labelling of trioctylphosphine oxide (TOPO)-and amino (AM) -capped semiconductor quantum dots (QD) CdSe/ZnS with functional ligands (dyes) of two types (pyridyl substituted porphyrins and heterocyclic pyridyl functionalized perylene diimide molecules) in liquid solutions and polymeric matrixes. [46][47][48][49][50][51][52][53][54][55] We have shown that depending on redox and electronic properties of interacting subunits as well as anchoring groups (connecting organic and inorganic counterparts) the formation of "QD-Dye" nanocomposites allows for a controlled realization of mutually relative (spatial) orientations and electronic energy scales in order to optimize intended photoinduced processes such as charge transfer, [56,57] fluorescence Foerster energy transfer (FRET) [20,46,47,50,52] or electron tunnelling in the conditions of quantum confinement (non-FRET process).…”
Section: Introductionmentioning
confidence: 99%